Pregnancy outcome after electrosurgical cervical cone biopsy using Fischer cone biopsy excisor. (1st February 2016) - Anwar, Ayesha; Igbenehi, Caleb; Lindow, Stephen W; Noor, Naheed; Musa, Siti; Saha, Arabinda
Abstract: Objective : To evaluate the pregnancy outcomes of all patients who underwent electrosurgical cone biopsy of the cervix between January 2000 and December 2011 and subsequently became pregnant. Study design : Retrospective cohort study. Settings : District General Hospital in the North East of England. Methods : Patients were identified from the local colposcopy electronic data, Hospital Episode Statistics and Maternity electronic data. Data were collected on a pro forma with two sections: (1) treatment section and (2) pregnancy section. In the treatment section, year and indication for treatment, volume of cervix removed, histological results and marginal status of specimen were documented. In the pregnancy section, time interval between treatment and pregnancy, pre-treatment obstetric history, cervical length measurements, cervical suture, gestation and mode of delivery and neonatal outcome were documented. Data were analysed using SPSS. Results : 25 women achieved 47 pregnancies after electrosurgical cone biopsy treatment. Most common indication for cone biopsy was glandular neoplasia accounting for nearly half of the procedures; 21.2% of pregnancies ended in first-trimester miscarriages. The preterm delivery rate (<37 weeks) was 19.4%. Volume of cervix excised was significantly greater in women who delivered preterm compared to women who delivered at term ( p  = 0.028). The rate of preterm delivery was significantly higher in post treatment pregnancies when compared to pregnancies before treatment in the same women ( p  = 0.02). The preterm delivery in post-treatment pregnancies was not related to the time interval between treatment and pregnancy ( p  = 0.54). There was no significant difference in miscarriage rates in pre- and post-treatment pregnancies ( p  = 0.98). Conclusion : Electrosurgical cone biopsy of cervix is associated with increased risk of preterm labour that is related to the volume of cervix excised.